Profitabilitas sebagai Mediator Pengaruh Risiko, Modal, Tata Kelola, dan Efisiensi terhadap Pertumbuhan Laba Bank - Yubileus, Fransisco; Azazi, Anwar; Ramadania, Ramadania; Mustika, Uray Ndaru (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study investigates the mediating role of profitability, as measured by Return on Assets (ROA), in the relationship between credit risk (Loan Loss Provision/LLP), capital adequacy (Capital Adequacy Ratio/CAR), operational efficiency (BOPO), and board size on Return on Equity (ROE) growth within Indonesia’s banking sector. The study is grounded in the growing competition in the industry and the demand for robust financial performance amidst the ongoing transformation from conventional to digital banking. The dataset comprises quarterly financial statements from 13 banks over the 2020–2024 period, yielding 260 total observations. Panel data regression and Sobel test-based mediation analysis were employed using EViews 12 software. The findings reveal that ROA significantly mediates the negative effect of LLP and BOPO on ROE growth, and positively mediates the influence of board size. Conversely, the mediating role of ROA in the relationship between CAR and ROE growth was not statistically significant. These results underscore the strategic importance of profitability in linking managerial and operational factors to the financial growth of banks. The practical implication highlights the need for banks to prioritize risk management and operational efficiency to support sustainable earnings growth.